2022
DOI: 10.3390/nu14194134
|View full text |Cite
|
Sign up to set email alerts
|

Treadmill Exercise Modulates Intestinal Microbes and Suppresses LPS Displacement to Alleviate Neuroinflammation in the Brains of APP/PS1 Mice

Abstract: Neuroinflammation occurs throughout the pathogenesis of Alzheimer’s disease (AD). Here, we investigated the effects of treadmill exercise on neuroinflammation in APP/PS1 transgenic AD mice and the potential involvement of microbe–gut–brain axis (MGB) mechanisms based on growing evidence that AD’s pathogenesis is correlated with a deterioration in the function of gut microbiota. APP/PS1 transgenic AD mice were subjected to 12 weeks of treadmill exercise, followed by spatial memory tests. After the behavioral st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 85 publications
3
11
0
Order By: Relevance
“…However, the neutral bacterium Prevotella was positively associated with mucin synthesis, which increases intestinal permeability and is an important condition for MA, leading to pro-inflammatory effects [ 24 ]. Several studies have shown that exercise can reduce the abundance of such bacteria and maintain intestinal health [ 58 , 59 , 60 ]. The current study also found that Alloprevotella rose after MA administration and fell after exercise intervention.…”
Section: Discussionmentioning
confidence: 99%
“…However, the neutral bacterium Prevotella was positively associated with mucin synthesis, which increases intestinal permeability and is an important condition for MA, leading to pro-inflammatory effects [ 24 ]. Several studies have shown that exercise can reduce the abundance of such bacteria and maintain intestinal health [ 58 , 59 , 60 ]. The current study also found that Alloprevotella rose after MA administration and fell after exercise intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The MICT protocol was performed as previously reported [29] . From week 1 to 8, the mice performed incremental aerobic exercises starting at 7 m/min and increasing to 14 m/min (Fig.…”
Section: Exercise Protocolmentioning
confidence: 99%
“…Running exercise has also been shown to increase the microbial content of Eubacteria , Roseburia , and Clostridia in the intestines of APP/PS1 mice, while decreasing the abundance of Prevotella , Bacteroides , Bacteroides fragilis , and L. johnsonii . This alteration inhibits the transfer of LPS to the brain, thereby alleviating LPS-induced neuroinflammation and improving cognitive function and pathological markers in AD mice [ 273 , 275 ]. Moreover, voluntary wheel running (VWR) exercise has been found to upregulate the abundance of phylum Bacteroidetes and genus Prevotella while reducing the abundance of phylum Actinobacteria and TM7 , as well as genus Oscillospira and Ruminococcus .…”
Section: Molecular Mechanisms Of Gut Microbiota Regulation Of Ad Lipi...mentioning
confidence: 99%